Shanghai rising : state power and local transformations in a global megacity - Chen, Xiangming (Professor of sociology) (Globalization and community, 2009)
"Until around 1990, Shanghai was China's premier but sluggish industrial center. Now at the beginning of the twenty-first century, the joint impact of global forces and state power has turned Shanghai into a dynamic megacity. Shanghai's remarkable growth in economy, infrastructure, and global presence has prompted questions about the Shanghai "miracle." This collection places the city's unprecedented rise in a rare comparative examination of U.S. cities, as well as with Asian megacities Singapore and Hong Kong, providing a nuanced account of how the Shanghai's politics, economy, society, and space have been transformed by macro- and micro-level forces"--Provided by publisher